Efeito Agudo em Parâmetros Cinéticos em Tarefas Estáticas e Dinâmicas devido ao Uso de Palmilhas Proprioceptivas - Calvo, Adriano Percival [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The use of additional somatosensory information favors the static and dynamic postural control. However, the comprehensiveness of devices to promote plenty of somatosensory information is still insufficient. An insole with forty semi-spheres of 5 mm in diameter distributed over its surface was designed to enhance tactile sensory information from the soles of the feet, thus improving biped and static upright postural control of adults, ordinary seniors and seniors individuals with Parkinson's Disease (PD). In the elderly living with PD, its effects were significant in static postural control and inexpressive effects in locomotion, whereas in other people it provided slightly positive effects. However, due to sample profiles and abilities assessed, such effects are not critical to deeply understand of the benefits/losses of the abundance of somatosensory information on human postural control due to the sample present deleterious effects of aging conjugate to degenerative disease of the CNS. The objective of this work was to evaluate the insole studied in static and dynamic conditions of postural control using a balance platform in order to understand the scale of the benefits/losses of this device in the human balance. To achieve this goal, three experiments were carried out. Twelve young male adults, avowedly healthy and left- handed to stand in one foot attended the study. In all tasks, the participants made three valid attempts using conventional insole [S] and proprioceptive insole [X]. In the first experiment, the participants remained in single leg orthostatic balance, for 10 seconds on a force balance platform alternating both support limbs. The results showed that the use of proprioceptive insole [X] mediolateral oscillation reduced in both limbs ([D] and [E]). In the second experiment, the participants performed the task of sitting and raisi... (Complete abstract click electronic access below)

O uso de informação somatossensorial adicional (i.e. tátil) favorece o controle postural estático e dinâmico. No entanto, a compreensão de dispositivos que promovem abundância das informações somatossensoriais ainda é insuficiente. Uma palmilha com 40 semiesferas de 5 mm de diâmetro sobre sua superfície foi desenvolvida para potencializar informações sensoriais táteis das solas dos pés e, consequentemente, proporcionar melhora no controle postural ereto, bípede e estático de indivíduos adultos, idosos e idosos vivendo com a doença de Parkinson (DP). Nos idosos vivendo com DP, seus efeitos foram expressivos no controle postural estático e inexpressivos na locomoção, enquanto nos demais públicos seus efeitos foram positivos, embora extremamente tímidos. Entretanto, estes efeitos não são norteadores para a compreensão profunda dos benefícios/prejuízos da abundância da informação somatossensorial sobre o controle postural humano em virtude da amostra estudada apresentar os efeitos deletérios do envelhecimento conjugado (ou não) à doença degenerativa do SNC. Portanto, pretendeu-se avaliar esta palmilha em condições estáticas e dinâmicas do controle postural por meio da Plataforma de Equilíbrio com o intuito de compreender a dimensão dos benefícios/prejuízos deste dispositivo no equilíbrio humano. Para atingir tal meta, foram realizados três experimentos. Em todos os experimentos participaram do estudo 12 adultos, declaradamente saudáveis e canhotos para equilíbrio unipodal. Em todas as tarefas, os participantes realizaram três tentativas válidas com uso de palmilha convencional [S] e proprioceptiva [X]. No primeiro experimento, os participantes permaneceram em equilíbrio ortostático unipodal por 10 segundos sobre uma plataforma de equilíbrio alternando ambos os membros de apoio. Os resultados mostraram que ... ( Resumo completo, clicar acesso eletrônico abaixo)
Optimization of electrical resistance welding process in PEI / continuous fibers composites foraeronautical application
Keywords: Biomecânica; Postura humana; Somatossensorial; Locomoção humana; Movimento; Propriocepção; Biomechanics